Methods identifying cost reduction potential for water electrolysis systems. (September 2021) - Badgett, Alex; Ruth, Mark; James, Brian; Pivovar, Bryan
Graphical abstract: Highlights: Methods of technoeconomic analysis for electrolysis are summarized. Costs of hydrogen produced from electrolysis are expected to decrease. Costs can decrease from R&D, economies of scale, and learning by doing. Performance gains include material reduction, substitution, and durability. Future topics of technoeconomic analysis for electrolysis areas discussed. Abstract : The electrochemical reduction of water to form hydrogen is an emerging alternative for energy storage, where hydrogen can be used as a transportation fuel, combusted to generate electricity, utilized in a fuel cell, or used as a feedstock for chemical synthesis. Techno-economic analysis (TEA) is a valuable tool for understanding how to inform research directions that could make hydrogen from electrolysis cost competitive with that produced by conventional means like steam methane reforming. The current state of knowledge on TEA of electrolysis systems suggests cost reductions are likely to result from advances in system design and materials, scale-up of manufacturing processes, and learning by doing effects as electrolysis deployment increases. Future directions and opportunities for TEA of electrolysis systems include dispatchable operation in wholesale power markets, optimization of capital cost and system durability, and analysis of pathways for hydrogen to support economy-wide decarbonization.